Sheep and goat production practice in agroforestry systems of Gedio Zone, Ethiopia - Debele, Selamawit; Habta, Matiwos (International Journal of Environment, 2015)
The study was conducted to describe sheep and goat production practice in three Agro-ecological Woredas of Gedio zone, southern Ethiopia. A set of semi-structured questionnaire was used to collect information from 120 sheep and goat owners based on single-visit-interviews. 32.6% of them participate in crop production, 56.5% of them involved in both animal and crop production and 5% of them involved in crop production, animal production and off farm activity. Sheep flock in the study sites were significantly different; and were 5.63, 6.97 and 3.4 in Wenago, Dilla and Kochera sites, respectively. Major feed resources were grazing (33.5%). The highest mortality rate occurred in suckling flock (16.24% lambs; 16.3% kids), young flock (9.64% lambs; 13.24% kids) and breeding females (ewes 12.06% and does 14.1%) in all study sites. Sheep and goat production in the studied areas was constrained by different problems; where the major ones are availability and cost of feeds, limitation of land for the expansion of production and poor extension services. Sheep and goats are very important smallholder producers due to their biological factors such as short generation interval, twinning, have short growth periods and do not require much space. DOI: http://dx.doi.org/10.3126/ije.v4i2.12658 International Journal of Environment Vol.4(2) 2015: 296-307